History of metal contamination in Lake Illawarra, NSW, Australia. (January 2015) - Schneider, Larissa; Maher, William; Potts, Jaimie; Batley, Graeme; Taylor, Anne; Krikowa, Frank; Chariton, Anthony; Zawadzki, Atun; Heijnis, Henk; Gruber, Bernd
Highlights: Lake Illawarra has a history of metal contamination. Metal concentrations were higher at the site closest to Port Kembla. The metals of highest concern were zinc and copper. Abstract: Lake Illawarra has a long history of sediment contamination, particularly by metals, as a result of past and current industrial operations and land uses within the catchment. In this study, we examined the history of metal contamination in sediments using metal analysis and 210 Pb and 137 Cs dating. The distributions of copper, zinc, arsenic, selenium, cadmium and lead concentrations within sediment cores were in agreement with historical events in the lake, and indicated that metal contamination had been occurring since the start of industrial activities in Port Kembla in the late 1800s. Most metal contamination, however, has occurred since the 1960s. Sedimentation rates were found to be 0.2 cm year −1 in Griffins Bay and 0.3 cm year −1 in the centre of the lake. Inputs from creeks bringing metals from Port Kembla in the northeast of the lake and a copper slag emplacement from a former copper refinery on the Windang Peninsula were the main sources of metal inputs to Lake Illawarra. The metals of highest concern were zinc and copper, which exceeded the Australian and New Zealand sediment quality guideline values at some sites. Results showed that while historical contamination persists, current management practices have resulted in reduced metal concentrations in surface sediments in the depositional zones in the centre of the lake.